Effects of Selected Nigerian Medicinal Plants on the Viability, Mobility, and Multidrug-Resistant Mechanisms in Liver, Colon, and Skin Cancer Cell Lines - AlQathama, Aljawharah; Ezuruike, Udoamaka F.; Mazzari, Andre L. D. A.; Yonbawi, Ahmed; Chieli, Elisabetta; Prieto, Jose M. (Frontiers in Pharmacology, 2020)
Medicinal plants indicated for chronic diseases usually have good safety margins as they are intended for lifelong treatments. We hypothesized that they may provide patients with baseline protection to cancers and multidrug resistance-reversing phytochemicals resulting in successful prevention and/or adjuvant treatment of chemotherapy-resistant cancers. We selected 27 popular herbal infusions widely used in Nigeria for diabetes and studied their effects on a panel of liver (HepG2), colon (Caco2), and skin (B16-F10) cancer cells. Cytotoxicity was measured using the SRB staining assay. The 2D antimigratory effect was evaluated using an Oris™ platform. The P-glycoprotein (P-gp) efflux activity was evaluated using Rh-123 as a fluorescent probe. The inhibition of tyrosinase-mediated melanogenesis was evaluated by colorimetric enzymatic assays. Our results show that melanoma cell proliferation was strongly inhibited by Anogeissus leiocarpus (Combretaceae), Bridelia ferruginea (Phyllanthaceae), D. ogea (Leguminosae), and Syzygium guineense (Myrtaceae) extracts (GI50 = 50 µg/ml). Alstonia boonei (Apocynaceae), Gongronema latifolium (Asclepiadaceae), and Strophanthus hispidus (Apocynaceae) were preferentially toxic against Caco2 (GI50 = 50, 5 and 35 µg/ml, respectively). The most active extracts against different drug resistance mechanisms were B. ferruginea (inhibition of P-gp efflux, and impairing tyrosinase activity) and X. americana (inhibition of P-gp efflux). A. leiocarpus, Kaya senegalensis (Meliaceae), S. guineense, and Terminalia avicennioides (Combretaceae) significantly inhibited B16-F10 cell migration. Lupeol, ursolic acid, quercitrin, epicatechin, gallic acid, and ellagic acid were dereplicated by HPLC and HPTLC as their bioactive phytochemicals. In conclusion, the above in-vitro activities of herbal infusions regularly consumed by Nigerian diabetic patients may either act as a baseline chemoprotection or as sensitizing agents.